Investigating the Effectiveness of Task-Based Language Teaching: A Comparison of Task-Based and Traditional Methods in Improving Language Skills - Midhat Meenahil; Eman Habib; Minahil Qureshi (JELLL, 2025)
This research paper explores whether Task-Based Language Teaching (TBLT) is better than old-school methods like the Grammar-Translation Method (GTM) and Direct Method for learning languages. By comparing TBLT with these traditional methods, we aim to see which one helps learners improve their language skills more effectively. Using an experimental research approach, we collected data from learners who experienced both TBLT and traditional methods. We used tests to measure language skills before and after the experimentation and gathered feedback from learners. Results show that although TBLT is more helpful in improving speaking, listening, reading, and writing skills compared to traditional methods, there is still a need to use methods like GTM depending on the learners’ context. TBLT involves interactive tasks that encourage real communication, making learning more engaging and independent. Traditional methods, on the other hand, focus more on memorization and rules. This study suggests that TBLT is a more efficient approach to learning languages, emphasizing the importance of practical, learner-centered methods in language education. However, sometimes it is better to use an eclectic approach to cater to the students’ required needs. Depending on the context and available resources, combining several different teaching methods or an eclectic way is the best strategy for maximum efficacy.